Classification of asthma severity levels using pulmonary acoustic signals based on wheeze sound - Syamimi Mardhiah Shaharum (School of Mechatronic Engineering, 2017)
As mentioned in the problem statements, CDSS that classify asthma to different severity levels using wheeze sound are not yet available. Thus, this work may answer many of the misconceived problems. As there are many symptoms present in asthma, respiratory sound signal were chosen to use in building the CDSS due to that wheeze that present as an adventitious lung sound signal are the most common symptoms present in asthma hence this thesis discussed on the previous literature in details. Due to that no such system is present; there is also no database present to be used for the system. Thus, the data acquisition for this research are develop based on the standardization method on lung sound auscultation present and are re-designed to be suited with the research. CORSA guidelines will be used to develop the data acquisition method for this research. This study focuses more in developing and proposing the best segmentation method as to that most of the previous study made neglected this part of the system. As for the classifier and the feature used, some of the most used methods from the previous study will be utilized, compared and finally selected to be implemented in the developed system. To avoid too many features from degrading the system, feature analysis and feature reduction will be done. Finally, a CDSS tool is developed to classify different severity levels of asthma from wheeze sound.